O ensino da eletrostática por meio de atividades experimentais com uso da aprendizagem significativa - NUNES FILHO, José Maria Almeida (2020)
This work proposes the study of electrostatic concepts through the use of experiments with alternative materials. The educational product that underlies this proposal consists of a guide of 18 experimental activities, accompanied by instructions for the construction of the necessary instruments, in addition to the entire discussion of the physical phenomena that involve the functioning of these instruments. The idea is that the student is the main element, participating in the making and manipulation of the experiments, in order to produce the necessary knowledge to understand some of the main concepts of electrostatics. The student is then an active subject, develops knowledge, the teacher's role is to guide and mediate this process. Within the assessment proposal, students were subjected to tests of quantitative approach, to assess whether there was improvement in the teaching-learning process, as well as to verify their satisfaction and involvement during the performance of the experimental activities. The previous results analyzed through the questionnaires, showed a significant improvement in the teaching-learning process of the students after the application of the work proposal. The use of experiments with alternative materials, proved to be an effective method compared to the traditional teaching model based on lectures.